Sleep As Preamble Of Optimal Health Among Elderly Hypertensive Adults - Alex, viji; A, Indira; V, Jayanthi; Mahammad, SS; G, Aruna; Thirunavukarasu, Ushakiran; A, Thirupathi (National Journal of Community Medicine, 2022)
Introduction: Healthy Aging is for everyone, not just those who are currently disease-free. Many factors influence the health of the elderly, including underlying physiological and psychological changes, health-related behaviour, disease status and also environments in which people are living strongly influence their health. Methodology: The 240 elderlies between the age group of 60-75 years from Primary Health Centre, Muthukur, Nellore, Andhra Pradesh, India was selected as study participants by simple random sampling technique and excluded those who were mentally and physically sick at the time of data collection. The Pittsburgh Sleep Quality Index (PSQI) scale was used to collect and Sleep promoting measures were taught and followed to experimental group for the period of six months. Results: In this study, the posttest mean PSQI sleep score among experimental group was 6.16 and control group was 7.95, with the mean difference was 1.79, as it was large and it was statistically significant difference at the value of t=3.34 at p≤ 0.001 level which indicate sleep promoting measures was effective to enhance sleep quality and to maintain normal blood pressure. Conclusion: Compared to the control group, the experimental group's elderly had better sleep quality; hence healthy sleep promoting measures are effective to manage and to maintain normal blood pressure.